The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1103/physrevlett.87.036802
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Fractal Patterns during a Classical-Quantum Transition

Abstract: We investigate how fractals evolve into nonfractal behavior as the generation process is gradually suppressed. Fractals observed in the conductance of semiconductor billiards are of particular interest because the generation process is semiclassical and can be suppressed by transitions towards either fully classical or fully quantum-mechanical conduction. Investigating a range of billiards, we identify a "universal" behavior in the changeover from fractal to nonfractal conductance, which is described by a smoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
47
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 19 publications
(36 reference statements)
6
47
0
Order By: Relevance
“…We now can use the semiclassical result (15) to estimate the value of the magnetic correlation field B C in recent experiments on FCF [2][3][4][5]. In these experiments, one has typically N c ∼ 2, n e ∼ 10 2 , A ∼ 1µm 2 and CL ∼ 10 −1 so that the correlation field is of the order of B C ∼ 10 −3 T. Some of these experiments [2][3][4] were performed with magnetic field values around or greater than B C ∼ 10 −3 T, which we believe to make the interpretation of the observed conductance fluctuations as genuine FCF ambiguous.…”
Section: Semiclassical Estimate For X Cmentioning
confidence: 99%
See 1 more Smart Citation
“…We now can use the semiclassical result (15) to estimate the value of the magnetic correlation field B C in recent experiments on FCF [2][3][4][5]. In these experiments, one has typically N c ∼ 2, n e ∼ 10 2 , A ∼ 1µm 2 and CL ∼ 10 −1 so that the correlation field is of the order of B C ∼ 10 −3 T. Some of these experiments [2][3][4] were performed with magnetic field values around or greater than B C ∼ 10 −3 T, which we believe to make the interpretation of the observed conductance fluctuations as genuine FCF ambiguous.…”
Section: Semiclassical Estimate For X Cmentioning
confidence: 99%
“…Triggered by the pioneer theoretical prediction by Ketzmerick [1], fractal conductance fluctuations (FCF) have been experimentally observed in semiconductor billiards by several groups [2][3][4][5]. These billiards are sub-micron sized electron cavities bounded by shaped walls and connected to twodimensional electron gas reservoirs by quantum point contact leads.…”
Section: Introductionmentioning
confidence: 99%
“…In semiconductor physics, chaotic electron transport has been explored using a variety of two-dimensional billiard structures [1][2][3][4][5][6][7][8][9][10], antidot arrays [1,2,[11][12][13] and resonant tunneling diodes containing a wide quantum well enclosed by two tunnel barriers [1,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Despite the diversity of the systems studied in these previous works, they all involve systems in which the transition to chaos occurs by the gradual and progressive destruction of stable orbits in response to an increasing perturbation.…”
Section: Introductionmentioning
confidence: 99%
“…First experimental data 14,15,16,17,18 appear to support this notion. However, in the corresponding numerical studies, no fractal structure in the conductance fluctuations could be found, 5,6,7,19 which, in part, has led to a number of theoretical works that propose alternative and sometimes even contradictory explanations for FCF.…”
mentioning
confidence: 92%
“…14,15,16,17,18 These experiments were in the regime where only a rather limited number of transmitting modes m, n = 2 − 6 is open. 15 Our results clearly show that the presence of soft walls in the experiment can be ruled out as the source for FCF at moderate k F . Note that this observation is in close correspondence to recent findings which suggest that "more complicated processes than those predicted in the semiclassical models are responsible for the observed behavior of FCF".…”
mentioning
confidence: 99%